Historical Temple of Dalem Balingkang: A Balinese Chinese Acculturation - Ida Bagus Agung Wicaksana (Bali Tourism Journal, 2021)
Dalem Balingkang temple depicts distinctive ornaments and interiors that resemble Chinese ambiance. It could be seen from the dominance of red and golden paints, architectural finishing, and Chinese shrine existence inside the main temple. The temple has been acknowledged as representing Balinese and Chinese customs acculturation that has existed for centuries. It was a palace for King Sri Haji Jaya Pangus who according to Purana Dalem Balingkang, reigned Bali in 1053 Isaka/1131 AD. However, due to some circumstances, the castle was left abandoned. Then a King from Pejeng, I Dewa Mayun Sudha, reconstructed the palace ruin into a temple to praise the late King and Queen of Dalem Balingkang. King Sri Haji Jaya Pangus’s marriage with the daughter of Chinese trader Kang Ching We became a significant momentum of the acculturation of two cultures, Balinese and Chinese. As upper-class citizens, their marriage set a new standard in society. Gradually some foreign habits and customs were absorbed in local daily life. It can be seen in various aspects of their life, from ritual, economic, religion, social, architecture, art and culture. Further, Balinese Chinese culture’s acculturation also occurred throughout Bali’s region and existed up to the moment.